Developing zeolitic imidazolate frameworks 67-derived fluorides using 2-methylimidazole and ammonia fluoride for energy storage and electrocatalysis. (15th January 2022) - Lee, Pin-Yan; Lin, Lu-Yin
Abstract: Zeolitic imidazolate framework 67 (ZIF67) with large surface area and tunable structure is one of the promising electroactive materials of electrochemical devices. In this study, NH4 F and nickel salt are applied to synthesize bimetallic ZIF67-derived fluoride for supercapacitor (SC) and electrocatalytic water splitting at the first time. Nickel with multiple redox states enhances energy storage and catalytic ability. NH4 F can confine crystalline growth and induce fluoride formation. Ratio of 2-methylimidazole to NH4 F for synthesis is optimized regarding to surface area and electrical conductivity. The highest specific capacitance (CF ) of 735.7 F/g at 20 mV/s is obtained for ZIF67-derived fluoride prepared using 2-methylimidazole to NH4 F ratio of 2 to 1, due to smaller particle size and high electrical conductivity. The symmetric SC shows the maximum energy density of 24.6 Wh/kg at 0.6 kW/kg. The CF retention of 100 % and Coulombic efficiency higher than 96 % are obtained in 6000 times charge/discharge process. The ZIF67-derived fluoride and IrO2 composite is fabricated as electrocatalyst for water splitting. This composite shows a high current density of 0.11 A/cm 2 at 1.6 VRHE and a small overpotential of 1.58 VRHE at 0.10 A/cm 2 . Current density retention of 100 % after continuous illumination for 600 min is also achieved. Graphical abstract: Image 1 Highlights: NH4 F and Ni salt are used to make bimetallic ZIF67-derived fluorides (ZIF67-F). The ZIF67-F is used for supercapacitor (SC) and electrocatalytic water splitting. Ratios of 2-melm to NH4 F is optimized regarding to surface area and conductivity. A specific capacitance (CF ) of 735.7 F/g at 20 mV/s is got for optimized ZIF67-F. The ZIF67-F and IrO2 composite shows a current density of 0.11 A/cm 2 at 1.6 VRHE .